Arguing and Thinking / A Rhetorical Approach to Social Psychology - Billig Michael (Cambridge University Press, 1996)
A breakthrough book in three different fields - sociology, psychology, and the rhetoric of inquiry. Acknowledgements, Second Thoughts and Second Arguments: A New Introduction, Antiquarian Psychology, Rules and Roles and Arguments, Protagoras and the Origins of Rhetoric, The Science of Persuasion, The Art of Witchcraft, Categorization and Particularization, Advocacy and Attitudes, Dilemmas of Common-Sense, The Spirit of Contradiction, Notes, References, Name and Subject Index.